Analisis Pengaruh Kualitas Layanan dan Strategi Pemasaran Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Pada Bank Bni Cabang Mattoangin - Nur Windah; Mashur Razak; Hendra Gunawan (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to analyze the effect of service quality and marketing strategy on customer loyalty, with customer satisfaction as a mediating variable at Bank BNI Mattoangin Branch. Customer loyalty is a strategic aspect for the banking industry in maintaining sustainable performance and competitive advantage; therefore, understanding the factors that influence it is essential. This study employs a quantitative approach using a survey method involving 83 customers of Bank BNI Mattoangin Branch, selected through purposive sampling. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software through a bootstrapping technique of 5,000 resamples to test both direct and indirect effects among variables. The results indicate that service quality and marketing strategy have a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction also has a positive and significant effect on customer loyalty and is able to mediate the relationship between service quality and marketing strategy on customer loyalty at Bank BNI Mattoangin Branch. These findings confirm that improving service quality and implementing effective marketing strategies play an important role in enhancing customer satisfaction and loyalty.